Divorce and remarriage in religious institutions: a case of Brethren in Christ church (BICC) Bulawayo Central - Nyathi, Ndabezinhle (Midlands State University, 2018)
Though marriage ideally was designed by God to last a life time, humankind has reduced it to a temporary and terminable social contract. The issue of divorce and remarriage remains a major issue in the African context. This study seeks to explore the aspect of divorce and remarriage in religious institutions. The study was carried out at Brethren in Christ Church (BICC) Bulawayo Central. It dwells on the concept of divorce and remarriage in general, bringing out the different perspectives associated with the subject. It clearly shows that remarriage and divorce are a living truth in society. This study was exploratory hence both quantitative and qualitative methods of research were used to come up with this study. The researcher used questionnaires and interviews to collect data which was then presented using pie chart, bar graphs and then further enhanced with content analysis. The research data was analyzed using the Statistical Package for Social Sciences (SPSS) and then data was presented in the form of bar graphs and pie charts. The study revealed congregants’ awareness levels towards the Biblical instruction on divorce and remarriage. The Western world takes a more liberal position on the issue of divorce and remarriage making it socially acceptable and free from scorn or condemnation. In the African context, a significant number of its religious institutions and communities continue to take a strict stance on divorce and remarriage thus considering it shameful, unacceptable and abominable. The study showed that for the Brethren in Christ Church, there were inconsistences in the application of the Holy Scriptures and the constitution in handling divorce and remarriage cases. Divorce and remarriage is unacceptable yet the BICC Bulawayo Central community continues to engage in it as evidenced by church records. The study showed that the consequences of such behavior were a disgruntlement amongst church members, levels of uncertainty and dissatisfaction. It was quite evident from the research that divorce and remarriage is a problem that can destabilize the religious institutions if the causes and effects are not well understood. The researcher suggests that to curb the problem there is need for proper application of the doctrine on issues of divorce and remarriage and situations surrounding the issue in order to promote harmony in the church. Congregational expectations for the leadership positions should be clearly articulated and members being sworn into posts should be informed of the constitutional aspects of divorce and remarriage as part of the induction process.